Drug-drug interactions in hospitalized older adults with acute coronary syndrome – a real-world study in Brazil - Tiago Aparecido Maschio de Lima; Moacir Fernandes de Godoy (Geriatrics, Gerontology and Aging)
Objective: Our aim was to determine the frequency of drug-drug interactions in clinical practice among hospitalized older adults diagnosed with acute coronary syndrome. Methods: This cross-sectional and descriptive study included 119 older adults with acute coronary syndrome who were admitted to a Brazilian public hospital. Potential drug-drug interactions were identified and classified using computerized databases. Adverse events were characterized according to severity, temporal relationship, causality, interactions as a determining factor, and traceability criteria. Results: Of the total sample, 30.25% of participants had ≥ 1 real drug-drug interaction. A total of 53 real drug-drug interactions were identified. The median number of real drug-drug interactions was 1 (maximum 3) per patient; 5.56% of those who experienced real drug-drug interactions died and 94.44% were discharged from hospital. Of the real drug-drug interactions, 47.17% were moderate and 41.51% were serious. Conclusions: Drug-drug interactions resulted in adverse reactions in hospitalized older adults with acute coronary syndrome in a real-world scenario in Brazil.